Dried Poultry Manure as Non-Protein Nitrogen Additive of Napier Grass (Pennisetum purpureum Schumach) Silage Fed to Sheep - Morbos, Clarita Ecleo; Bantugan, Sulpecio C.; Bestil, Lorina C. (Annals of Tropical Research, 2018)
The study was conducted to describe the physical characteristics of napier grass silage added with dried poultry manure (DPM) as non-protein N source, and to assess its acceptability and digestibility in sheep. Three types of silages were evaluated: T1 – napier grass alone, T2 – napier grass + DPM (at a ratio containing 10% crude protein), and T3 – napier grass + DPM (at a ratio containing 12% crude protein). These were stored in airtight plastic drum silos for 45 days at room temperature. After evaluation, the silages were tested with 9 male growing sheep for intake and digestibility measurements arranged in completely random fashion. Physical evaluation in terms of color, smell, and texture of the 3 silages showed no significant differences, and all showed good quality silage characteristics. However, significantly higher pH level (p<0.05) approaching normal rumen pH was observed in silages containing DPM (T2 and T3) compared to that without (T1). Chemical analysis showed significantly higher dry matter (DM) and crude protein (CP) contents in T2 and T3 silages than in T1. The OM content, however, was significantly reduced with the addition of DPM (T2 and T3) than without (T1) while acid detergent fiber (ADF) and neutral detergent fiber (NDF) contents showed no significant differences. Nutrient intakes significantly increased with silages containing DPM (T2 and T3) while increases in nutrient digestibility by sheep for the 3 silages showed no significant differences in all parameters measured. The addition of DPM to napier grass silage to contain 10 to 12% CP is recommended to increase CP and DM contents and improve nutrient intakes without affecting nutrient digestibility.